Effectiveness of leaflet and video interventions in promoting disease prevention behaviors among online motorcycle taxi drivers in Medan City - Surbakti, Tiara Lorensia Br; Azzahra, Avivani; Dameria; Wau, Herbert (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Online motorcycle taxi drivers represent informal sector workers who are at high risk of experiencing various health problems, such as musculoskeletal disorders, respiratory issues, and occupational stress, due to exposure to pollution, non-ergonomic working postures, long working hours, and unsafe road conditions. This study aims to identify the characteristics of online motorcycle taxi drivers in relation to the improvement of disease prevention behaviors. The research employed a quantitative approach with a non-randomized pretest–posttest control group design. The study population consisted of all online motorcycle taxi drivers operating in the Universitas Prima Indonesia area, with a total sample of 60 participants. They were divided into two groups: 30 respondents who received health education through leaflet media (intervention group) and 30 respondents who received education through video media (control group), selected using a non-probability sampling technique. Among respondents in the leaflet group, the majority were aged 19–44 years (93.3%), had a high school education (76.7%), had worked for less than five years (63.3%), worked more than eight hours per day (73.3%), and used automatic motorcycles (53.3%). Similarly, in the video group, most respondents were aged 19–44 years (90%), had completed high school (63.3%), had worked for less than five years (76.7%), worked more than eight hours per day (73.3%), and used automatic motorcycles (63.3%). Online motorcycle taxi drivers are part of the informal workforce with high health risks, highlighting the need for preventive efforts through educational interventions. The study findings indicate that the majority of respondents in both the leaflet and video groups were young adults with high school education, short work tenure, long working hours, and predominantly used automatic motorcycles. These characteristics can serve as a basis for designing more targeted health interventions to enhance disease prevention behaviors.